Pelaksanaan Hizbul Wathan sebagai Penguat Kecerdasan Emosional Siswa di SD Muhammadiyah 5 Surakarta - Rahmawati, Dwiki Nur, Drs. Saring Marsudi, SH. M.Pd (2017)
This study aims to: 1) To describe the implementation Hizbul Wathan in SD Muhammadiyah 5 Surakarta. 2) lyzetheactivities that can strengthen the emotional intelligence of students in the activities of Hizbul Wathan in SD Muhammadiyah 5 Surakarta. 3) To identify the factors supporting and ibiting factors strengthening the emotional intelligence of students on the implementation of Hizbul Wathan in SD Muhammadiyah 5 Surakarta. The research is a qualitative research with qualitative descriptive design. The informants are incipals, coaches HW and classroom teacher. Data collection techniques used were observation, interviews, and umentation.Mechanical analysis includes data reduction, apresentation,verification and inference. The validity of research data using a ngulation of sources and methods. The results showed that 1) The Hizbul Wathan: builder named Mr. Sugiyarto and Mr. Jemy, who participated in the HW 3-5 grade students, the implementation is done every Saturday at 10:50 to 12:00 in classroom 3, the activities carried pat, songs and scouting skills, according to the nature and implementation is already scouting mission. 2) The activities that can strengthen the emotional intelligence: yells, rigging, dragbars,regulations marching, Outbound.3) Supporting Factor amplifier: a means of infrastructures, good communication, learning environment, enthusiastic. Inhibiting factors: the character of the child, the shortage of coaches, lack of books and the ability of the builder, not timely, family environment, parents. This study therefore concluded that the implementation of the Hizbul Wathan can strengthen the emotional intelligence of students in SD Muhammadiyah 5 Surakarta.Keywords: Hizbul Wathan, emotional intelligence